Study on the behaviour of repaired reinforced concrete (RC) concrete elements. - Abd. Hamid, Hazlan; Makhtar, Ahmad Mahir; Awang, Abdullah Zawawi; Omar, Wahid (Universiti Teknologi Malaysia, 2002)
Carbon FRP has recently being used as strengthening elements of reinforced concrete elements such as beams. Two sets of experiments was carried out to study the behaviour beams strengthened with FRP fabric wrap and beams strengthened with FRP plates. The first set consists of 3 beams; a control beam, a beam reinforced with FRP plates, and a pre-cracked beam reinforced with FRP plates. Observations were made on the ultimate load capacity, load-deflection behaviour, crack pattern and propagation of tested beams. Ultimate load capacity of strengthened beams increased by more than 20% when compared to control beam. Strengthened beams also exhibited improved load-deflection behaviour and crack pattern and propagation behaviour. The behaviour of the pre-cracked beam was almost the same as the uncracked beam. The second set of 3 beams was designed with no shear reinforcement so that the beams would fail in shear. Two of the beams were wrapped with FRP fabric wrap while one acts as control. One of the wrapped beams was wrapped with one layer 90o to the horizontal while the other was wrapped with two layers; one at 45o and the other at –45o to the horizontal. Load carrying capacity and load-deflection behaviour of all beams tested were observed. From the results of the experiments it can be seen that the load carrying capacity of the strengthened beams wrapped at 90o to the horizontal almost doubled when compared while the other wrapped beam more than double its load carrying capacity. From the experiments, it is shown that both FRP plates and fabric wrap strengthened beams that were misdesigned or damaged which should encourage their use it the repair of structural elements amongst practitioners.